Role of Refresher Course in the Professional Development of Librarians - Ghuman, Surinder Singh (Journal of Information and Knowledge, 2013)
Continuous changing environment in and around the libraries have necessitated the participation in refresher courses by the librarians. These courses provide a proper place and opportunity where librarians can think, learn, analyze and can do their self introspection. University Grants Commission is providing infrastructure for the smooth conduct of these courses. Refresher course provides a platform where working librarians, technical experts, teachers meet to discuss the present scenario of the library and information science and exchange ideas which mutually benefit each other. Attempt has been made to study the role need, use and objectives of the refresher course.